Initial scabies diagnosed by history. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Two 8-month-old dizygotic twins were first observed because one of them (Fig. 1) had a left parotid hemangioma, and because both had an identical erythematous, papular vesicular rash on the trunk, which had begun simultaneously a week earlier. The eruption had not been preceded by fever or other problems and was not itchy. Physical examination (Fig. 1, 2) showed papular vesicular lesions, often surrounded by intense erythema. The baby-sitter who assisted the twins from 14 days had many burrows of the hands from which the scabies mite was isolated, whereas the search for mites was negative in both the twins. Although there were no classic lesions in classic sites and despite the absence of itching, we prescribed permethrin 5%, leading to a rapid regression of the lesions and thus confirming the suspicion of scabies.